High Energy, Optical, and Infrared Detectors for Astronomy V 2012
DOI: 10.1117/12.925379
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherical infrared focal plane arrays: a new design parameter for the instruments

Abstract: In ground based astronomy, mainly all designs of sky survey telescopes are limited by the requirement that the detecting surface is flat whereas the focal surface is curved. Two kinds of solution have been investigated up to now. The first one consists in adding optical systems to flatten the image surface; however this solution complicates the design and increases the system size. Somehow, this solution increases, in the same time, the weight and price of the instrument. The second solution consists in curvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Briefly the focalization surface of a spherical lens is not a flat plane but a curved concave shape close to a spherical shape. By curving a Focal Plane Array (FP A), one can correct this aberration without extra corrective lenses [4]. This can be applied to terrestrial and spatial telescopes [5] and very compact high-performance cameras [6].…”
Section: Introductionmentioning
confidence: 98%
“…Briefly the focalization surface of a spherical lens is not a flat plane but a curved concave shape close to a spherical shape. By curving a Focal Plane Array (FP A), one can correct this aberration without extra corrective lenses [4]. This can be applied to terrestrial and spatial telescopes [5] and very compact high-performance cameras [6].…”
Section: Introductionmentioning
confidence: 98%
“…This achievement was done by adapting the curving process developed by Dumas and Fendler published in 2012 for bolometric arrays working at room temperature and at a wavelength of 11µm (cf Fig.1 middle). This group also worked on the optical design optimizations of the proposed instrumentation for the E-ELT (Fendler+ [8]) by use of curved focal planes, demonstrating a global increase in performance with the use of less component, less complex. They also demonstrated that a major issue in their process was the curving of convex detectors, for mechanical reasons, that degrades the shape and the performance.…”
Section: A Static Curvaturementioning
confidence: 99%
“…As explained by Rim et al [4] or Fendler & Dumas [8][9] [10], the curvature of focal plane arrays leads to a drastic simplification of the optical systems by offering a new parameter in the optimizations. The field curvature, composed to first order by the Petzval curvature and the astigmatism aberration, no more has to be compensated by a set of complex optics flattening the field.…”
Section: A Static Curvaturementioning
confidence: 99%
“…As explained by Rim et al or Fendler & Dumas [8][9] [10], the curvature of focal plane arrays leads to a drastic simplification of the optical systems by offering a new parameter in the optimizations. The field curvature, so called the Petzval surface, no more has to be compensated by a set of complex optics flattening the field.…”
Section: Static Curvaturementioning
confidence: 99%
“…This achievement was done by adapting the curving process developed by Dumas and Fendler published in 2012 for bolometric arrays working at room temperature and at a wavelength of 11µm ( Figure 1). This group also worked on the optical design optimizations of the proposed instrumentation for the E-ELT (Fendler+ [8]) by use of curved focal planes, demonstrating a global increase in performance with the use of less component, less complex. They also demonstrated that a major issue in their process was the curving of convex detectors, for mechanical reasons, that degrades the shape and the performance.…”
Section: Static Curvaturementioning
confidence: 99%